Factors related to enrolment in early therapy services following neonatal intensive care unit discharge. (12th December 2020) - Heiny, Elizabeth; Wolf, Sarah; Collins, Margaux; Durant Kellner, Polly; Pineda, Roberta
Abstract: Aim: Early therapy can improve developmental outcomes for preterm infants. However, preterm infants who are referred have low enrolment in early therapy services following neonatal intensive care unit (NICU) discharge. This manuscript aims to investigate the relationship between infant medical and sociodemographic factors and enrolment in early therapy services post‐NICU discharge, when system‐related barriers to access are minimised. Methods: This was a retrospective investigation of 89 families with infants born ≤32 weeks of gestation. Families were approached for enrolment into early therapy services following NICU discharge through Baby Bridge programming, which aims to improve access to therapy services following NICU discharge. Results: Seventy‐three (82%) families enrolled in early therapy services, and 16 (18%) families declined. Parents were more likely to enrol in early therapy if they had public insurance ( P = 0.01), a maternal psychiatric diagnosis ( P = 0.02) or additional children under 18 years in the home ( P = 0.01). No infant medical factors were related to enrolment. Conclusion: Although enrolment rates were high, 18% of families refused therapy services, despite removing system‐related barriers to access. Targeted interventions can be developed to increase enrolment in early therapy services among populations who are most likely to refuse therapy services after NICU discharge.